Synthesis of Silicas with Carboxyl Functionality Using Template Method - O. A. Dudarko; D. S. Bakulina; Yu. L. Zub (Хімія, фізика та технологія поверхні)
A one-step method of synthesis of new materials with acidic carboxylic groups, based on the template method, has been developed. It was found that the postsynthetic treatment of silicas in boiling HCl leads to changes in structural parameters and changes the nature of functional groups. Efficiency of the methods was demonstrated by powder X-ray diffraction, infrared spectroscopy, and thermal analysis.